Bridges or walls: remarks on translating the concepts of cultural - historical theory - Elizabeth Tunes; Zoia Ribeiro Prestes (Вестник Московского университета. Серия 14: Психология)
Background. The problem of translating scientific articles into other languages affects not only translators but also psychologists, since the accuracy of translation determines the adequacy of understanding and transferring of scientific concepts. Objectives. The article focuses on the critical discussion of different variants in translating some concepts of L.S. Vygotsky's cultural-historical theory into Portuguese. Study Materials. This article discusses the concepts of the “zone of proximal development”, “learning”, and “speech”. Results. The paper considers variations in the translations of L.S. Vygotsky's concept of the cultural-historical theory into Portuguese. Insufficient attention of translators to the theoretical and methodological foundations of the original scientific text, which generates substantive errors in translation and distorts (simplifies) the content of the original approach, is critically discussed. Conclusions. Both literary and scientific translation should be understood as an unfinished process that requires constant revision and improvement. The philosophical, ethical and historical ideas of the translated author should be the basis for this. Only in this case will translation contribute to the communication and connection of people speaking different languages.